"Day or night, no matter what, I will go": Women's perspectives on challenges with follow-up care after cervical cancer screening in Iquitos, Peru: a qualitative study - Rachel M. Morse; Magdalena Jurczuk; Joanna Brown; Lita E. Carrillo Jara; Graciela Meza; E. Jennifer Ríos López; J. Kathleen Tracy; Patti E. Gravitt; Valerie A. Paz-Soldan; the Proyecto Precancer Study Group (BMC, 2023)
Abstract Background The study's objective was to explore the factors associated with loss to follow-up among women with abnormal cervical cancer screening results in Iquitos, Peru from women's perspectives. Methods In-depth interviews were conducted with 20 screen-positive women who were referred for follow-up care but for whom evidence of follow-up was not found. Interview transcripts were thematically analyzed inductively, and the codes were then categorized using the Health Care Access Barriers Model for presentation of results. Results All interviewed women were highly motivated to complete the continuum of care but faced numerous barriers along the way, including cognitive barriers such as a lack of knowledge about cervical cancer and poor communication from health professionals regarding the process, structural barriers such as challenges with scheduling appointments and unavailability of providers, and financial barriers including out-of-pocket payments and costs related to travel or missing days of work. With no information system tracking the continuum of care, we found fragmentation between primary and hospital-level care, and often, registration of women's follow-up care was missing altogether, preventing women from being able to receive proper care and providers from ensuring that women receive care and treatment as needed. Conclusions The challenges elucidated demonstrate the complexity of implementing a successful cervical cancer prevention program and indicate a need for any such program to consider the perspectives of women to improve follow-up after a positive screening test.